Marine Mammals - Abdelhay Essayed Kaoud, Hussein (IntechOpen, 2022)
This book offers a broad perspective on marine mammal species and populations considered to be most at risk due to human activities. It emphasizes the importance of understanding the essential biology and ecology of marine mammals to assess the correlates and causes of extinction and to implement science-based conservation. Chapters address such topics as different types of marine mammals and their importance to the ecosystem of the world's oceans and food cycles, lactation in marine mammals, dolphin survival rates and causes of movement reduction in Bangladesh, and much more.